The Effects of the Substrate Length and Cultivation Time on the Physical and Mechanical Properties of Mycelium-Based Cushioning Materials from Salix psammophila and Peanut Straw - Xiaowen Song; Shuoye Chen; Jianxin Wu; Ziyi Cai; Yanfeng Zhang; Risu Na; He Lv; Cong He; Tingting Wu; Xiulun Wang (Biomimetics)
Mycelium-based biocomposites represent a novel class of environmentally friendly materials. This study investigated the potential of using Salix psammophila and peanut straw as substrates for cultivating Pleurotus ostreatus and Ganoderma lucidum, respectively, to fabricate mycelium-based cushioning materials. The results demonstrated that the Pleurotus ostreatus-based cushion material using Salix psammophila (POSM) outperformed the Ganoderma lucidum-based cushion material using peanut straw (GLPM) in terms of overall performance. Both materials presented optimal comprehensive properties when the cultivation period reached 30 days. Increasing the substrate length enhanced most of the material properties. The resulting density ranged from 0.13 to 0.16 g/cm3, which was higher than that of polystyrene foam. The contact angles of both materials exceeded 120°, whereas their elastic springback rates reached 50.2% and 43.2%, and their thermal conductivities were 0.049 W/m·K and 0.051 W/m·K, respectively. Additionally, thermogravimetric analysis revealed that both materials exhibited similar thermal degradation behavior and relatively high thermal stability. These findings align with those of previous studies on mycelium composites and indicate that the physical and mechanical properties of the materials are largely comparable to those of expanded polystyrene (EPS). In conclusion, the developed mycelium-based cushioning materials promote the efficient utilization of agricultural residues and hold promise as a sustainable alternative to EPS, offering broad application prospects in the transportation and packaging sectors.